SIR PLEASE PROVE

Asked by gunjansingh | 6th Dec, 2009, 06:10: PM

Expert Answer:

(cosecA - secA ) ( cotA -  tanA) =

[(cosA - sinA)/(cosAsinA)][(cos2A - sin2A)/(cosAsinA)] =

[(cosA - sinA)(cosA - sinA)(cosA + sinA)]/(cosAsinA) =

[(cosA - sinA)2(cosA + sinA)]/(cosAsinA) =

[(cos2A + sin2A - 2sinAcosA)(cosA + sinA)]/(cosAsinA) =

[(1 - 2sinAcosA)(cosA + sinA)]/(cosAsinA) =

[(1 - 2sinAcosA)/(cosAsinA)][(cosA + sinA)/(cosAsinA)] =

(secA cosecA -2 )(cosecA + secA )

Regards,

Team,

TopperLearning.

Answered by  | 6th Dec, 2009, 07:28: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.